“You Must Attend to My Wedding Party”: The Power of Punjungan as a Symbol of Wedding Invitation - Umar Alfaruq A. Hasyim; Nurul Puspita; Zulqurnain Sabir; Julie Simon Macariola (Anglophile Journal, 2022)
Punjungan is a tradition of giving meals to the neighbor for expressing gratitude. It had been happened for long time, however this tradition is still applied by Javanese in Indonesia. Moreover, It is also implemented by Javanese who live in Central Lampung. This research aims at revealing the values of the punjungan and the consequences of this custom among the community. Moreover, this study used Pierces’ Semiotics analysis and the theory of gift by Strauss. It is descriptive qualitative research that used interview and observation as the way to collecting data. Then, the data analyzed interactively. The data obtained from respondent of central Lampung citizen especially Sritejokencono village. It was found that the tradition is still applied and has a function as an invitation that has consequences for the receiver to attend the invitation. This research is useful for the society in order to avoid miscommunication among them. Keywords: Pierces Semiotics Analysis, Punjungan as Symbol, Analysis of Semiotic